Replication Data for: Costs and benefits of climate-smart agriculture: The case of the Dry Corridor in Guatemala - Sain, Gustavo; Loboguerrero Rodriguez, Ana María; Corner-Dolloff, Caitlin; Lizarazo, Miguel; Nowak, Andreea C.; Martínez Barón, Deissy; Andrieu, Nadine (International Center for Tropical Agriculture, 2016)
Central American countries, particularly Guatemala, are experiencing extreme climate events which are disproportionately affecting agriculture and subsequently rural livelihoods. Governments are taking action to address climatic threats, but they need tools to assess the impact of policies and interventions aiming to decrease the impacts of climate change on agriculture. This research, conducted with national policy makers and climate change and agriculture stakeholders in Guatemala, provides a comparative analysis of eight climate-smart agriculture (CSA) practices and technologies associated with the smallholder maize-beans production system in the Dry Corridor. The practices were identified as high-interest for investment by national stakeholders. CSA practices and technologies aim to improve food security, resilience, and low emissions development, where possible and appropriate. The paper assesses the cost-benefit profile of the introduction of CSA options into farm production systems. Indicators related to profitability and valuation of environmental and social externalities are used to assess options. Probabilistic cost-benefit analysis (CBA) is used to address field variability and high uncertainty around parameter values. All practices except one were profitable over their lifecycle, with some practices, expected to be ideal for drought prone areas, presenting a higher risk for adoption. The results were discussed with national stakeholders who established best-bet CSA investment portfolios. This paper argues that a thorough understanding of the costs and benefits of potential CSA options is needed to channel investments effectively and efficiently towards both short- and long-term interventions and should be coupled with broader assessment of trade-offs between CSA outcomes.